2011
DOI: 10.1128/aac.00620-11
|View full text |Cite
|
Sign up to set email alerts
|

A Translation Inhibitor That Suppresses Dengue Virus In Vitro and In Vivo

Abstract: We describe a novel translation inhibitor that has anti-dengue virus (DENV) activity in vitro and in vivo. The inhibitor was identified through a high-throughput screening using a DENV infection assay. The compound contains a benzomorphan core structure. Mode-of-action analysis indicated that the compound inhibits protein translation in a viral RNA sequence-independent manner. Analysis of the stereochemistry demonstrated that only one enantiomer of the racemic compound inhibits viral RNA translation. Medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Virus-specific inhibitors have been identified that target the viral envelope (13), methyl transferase (14), protease (15), NS4B protein (16), polymerase (17,18), and virus-specific RNA translation (19). In addition, compounds that target host enzymes, such as ER glucosidases (20)(21)(22)(23), dihydroorotate dehydrogenase (19), and an intracellular cholesterol transporter (24), have been shown to have antiviral activity. Although these compounds appear to be effective at inhibiting DENV replication, there is still no approved antiviral therapeutic for the treatment of DENV infection in humans.…”
mentioning
confidence: 99%
“…Virus-specific inhibitors have been identified that target the viral envelope (13), methyl transferase (14), protease (15), NS4B protein (16), polymerase (17,18), and virus-specific RNA translation (19). In addition, compounds that target host enzymes, such as ER glucosidases (20)(21)(22)(23), dihydroorotate dehydrogenase (19), and an intracellular cholesterol transporter (24), have been shown to have antiviral activity. Although these compounds appear to be effective at inhibiting DENV replication, there is still no approved antiviral therapeutic for the treatment of DENV infection in humans.…”
mentioning
confidence: 99%
“…Detailed mechanism-of-action studies, breadth of antiviral activity outside the alphavirus genus, and in vivo activity were not explored with this natural product-derived compound, so a more detailed comparison with CCG205432 and related compounds is not yet possible. However, Wang et al recently described a novel benzomorphan compound (NITD-451) with in vitro and in vivo antiviral activity (45) that shares intriguing contrasts with our indole-2-carboxamide compounds. The benzomorphan series of compounds were first developed as antivirals against DENV, and NITD-451 shows potent activity against several flaviviruses but not WEEV, whereas CCG205432 is active against WEEV and related alphaviruses but not DENV.…”
Section: Discussionmentioning
confidence: 92%
“…The benzomorphan series of compounds were first developed as antivirals against DENV, and NITD-451 shows potent activity against several flaviviruses but not WEEV, whereas CCG205432 is active against WEEV and related alphaviruses but not DENV. Furthermore, although both series of compounds have enantiospecific activity and modulate cellular gene expression, NITD-451 suppresses translation in cells and in in vitro assays (45), whereas CCG205432 was active only in cells and did not inhibit expression from mRNA templates in vitro, suggesting different mechanisms of action. However, Wang et al were also unable to generate NITD-451-resistant DENV, similar to our failed attempts to generate CCG205432-resistant WEEV and FMV, consistent with both compounds having host factors as targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteolysis of the dengue virus genome yields three structural and seven nonstructural proteins [6]. During viral maturation, the polyprotein is cleaved by the NS3 serine protease at the N-terminal domain, interceded by the cofactor NS2B [7]. Processing of this polyprotein is a fundamental process that must occur before viral RNA replication process.…”
Section: Introductionmentioning
confidence: 99%